(untitled) (Medico Legal Update, 2021)
In order to determine the prevalence of Pseudomonas aeruginosa among hospitalised patients, 156 specimens were collected from hospitalized patients referring Baghdad, Iraq hospitals. Bacterial isolates were identified using conventional biochemical tests and then identification was confirmed by the locating of 16SrRNA. Pseudomonas aeruginosa constitutes 30.05%. In conclusion, the attention should be paid toward the infections of this opportunistic pathogen.